Yield and viability of quinoa seeds as affected by planting arrangement - de Oliveira Filho, Antonio Francelino; Neurilan Costa Silva, Maria; Innecco, Renato; Coelho Bezerra, Francisco Thiago; de Abreu, Wesley Eusébio; Trindade Viana, Ítalo Emerson (Comunicata Scientiae, 2021)
Quinoa has great capacity to diversify agricultural production, due to its characteristics as functional food, rich in protein and fibers, besides presenting drought tolerance and high phenotypic plasticity. The objective of this study was to evaluate the effects of population and crop year arrangements on seed production and physiological potential of BRS Piabiru quinoa cultivar. The experiments were conducted in the experimental area of the Plant breeding Department of the Federal University of Ceará, at the Pici Campus, in Fortaleza, CE for two agricultural years (2014/2015 and 2015/2016) under irrigated regime. The treatments resulted from a 3x3 factorial scheme (3 spacings between rows: 20, 40 and 60 cm and 3 planting densities within the row: 10, 15 and 20 cm), and these treatments were distributed in four randomized blocks. The physiological tests of the seeds were carried out in the same seed laboratory institution. The mass of 1000 seeds, %U, IVG, TMG, %G, accelerated aging, panicle length and productivity were evaluated. The seeds produced in the different planting arrangements showed high physiological quality, and the agricultural year was determinant. Increasing planting density reduced panicle size and increased quinoa productivity during the two cycles.